2014
DOI: 10.1212/wnl.0000000000000643
|View full text |Cite
|
Sign up to set email alerts
|

Neurofluctuation in patients with subcortical ischemic stroke

Abstract: Objective: The purpose of this study was to assess the incidence of deterioration, fluctuation, and associated risk of poor outcome in patients with subcortical stroke (SCS). Methods:We conducted a prospective observational study, enrolling patients admitted with SCS based on their clinical examination and imaging studies. An NIH Stroke Scale evaluation was performed daily and whenever deterioration in examination was detected. Neurologic deterioration was defined as a motor score increase of at least 1 on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…In the present study, we did not observe such an association. Our results were consistent with one recent study in the literature 5 ) . However, these findings must be validated in larger, multi-center studies in the future.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, we did not observe such an association. Our results were consistent with one recent study in the literature 5 ) . However, these findings must be validated in larger, multi-center studies in the future.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have reported the prevalence of END to be approximately 21%–50% in patients with MIS 4 , 5 ) . Using this estimate, we calculated a minimum sample-size requirement of 310 patients for determining the true incidence rate within ± 15% with 95% confidence.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…Recurrent TIA was included given its inclusion in prior risk-stratification scores 11 as an important outcome; neurological deterioration was included given evidence that it can cause long-term disability 14 and was used in prior TIA-S clinical trials. 4 Recurrent TIA-S included new neurological symptoms in the absence of hemorrhage on brain imaging, not attributable to any other medical condition and confirmed clinically or by imaging.…”
Section: Methodsmentioning
confidence: 99%
“…Early neurological deterioration (END) is fairly common in patients with acute IS, and is associated with increased morbidity and mortality (Vahidy et al, 2014;Yi, Han, Zhou, Lin, & Liu, 2016). It is very important to investigate the mechanisms of END, and prevent this detrimental event.…”
Section: Backg Rou N Dmentioning
confidence: 99%